Effects of using lubricant during the speculum examination for Pap smear collection. Issue 12 (3rd October 2018) - Nunes, Rodrigo Dias; Cascaes, Maisa; Schneider, Ione Jayce Ceola; Traebert, Jefferson
Abstract : Objective: To evaluate the effect of using lubricant during speculum examination for Pap smear collection. Methods: A cross‐sectional study was conducted involving 83 patients attending a medical school clinic. Participants were allocated into two groups: Group 1—Lubricant using; Group 2—No lubricant using. All patients were submitted to two successive collections and after were asked about their level of discomfort. Differences between groups regarding quality, artifacts, cytology, and level of discomfort were observed through chi‐squared test. Odds ratios and 95% confidence intervals were also estimated. Statistical significance was set at P < .05. Results: No significant differences between groups regarding quality, presence of artifacts, and cytological results were observed. Significant lower discomfort level in Group 1 (lubricant using). Conclusion: The use of vaginal lubricant did not affect the results of cytology and could be a useful tool to reduce the discomfort during Pap smear collection.